Art and Body Expression: the Fusion for Teach Teachers - Catalina Rigo Vanrell; Rosaura Navajas Seco (Arteterapia)
The fusion of two artistic languages as they are the plastic art and the corporal expression forms a symbiosis that enriches to all the one that gets the experience. Its main objective is to express in all its dimensions the value of creating and the freedom to show internal sensations that they favour the personal growth. A carried out experience in the Complutensian University with students and of all countries. This experience makes us understand that the coexistence of these two disciplines can develop competencies and abilities to be better person.